The Influence of China’s International Economy on the United States’ Economic Dominance after the Cold War - Brichi, Abir; Abderrahim, Rouguia Nour El Houda; Mihoubi ,Ahmed (Faculty of Letters and Foreign Languages Department of English, 2017)
This dissertation aims at discussing whether China will become the new leader of the world because of its current powerful economic status. To fulfil this aim, statistics and data will be described, compared, and analysed. The analysed data indicate that the US is stronger and more dominant than China in the field of international economy, although China is the world’s largest exporter. When it comes to the US and China’s bilateral trading system, none of them imposes their ideology, policy, or principal on the other because they trade according to the World Trade Organization laws and regulations. The findings of the dissertation show that China’s international economy will not be stronger than the US’s.